1970
DOI: 10.2337/diab.19.6.429
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin Release by Pancreatic Glucagon

Abstract: In order to localize the site of its insulinogenic stimulus, glucagon was infused individually into the pancreas, liver, and peripheral circulation of normal dogs. Blood levels of insulin, glucose and nonesterified fatty acids were monitored in the femoral artery, portal and hepatic veins. The pancreatic artery infusions provoked a more rapid and marked insulin release initially than the same amount of glucagon given into the portal or femoral vein. The degree of hyperglycemia was comparable in the three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…22 It is possible that our pancreatic casein injection acted on the alpha cells to release glucagon which in turn caused insulin secretion. Our previous data 15 have demonstrated that epinephrine fails to inhibit glucagon stimulation of the beta cells. Therefore, present findings indicate that the intravenous amino acid response is .no more dependent upon glucagon than the glucose response, since epinephrine blocks both.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…22 It is possible that our pancreatic casein injection acted on the alpha cells to release glucagon which in turn caused insulin secretion. Our previous data 15 have demonstrated that epinephrine fails to inhibit glucagon stimulation of the beta cells. Therefore, present findings indicate that the intravenous amino acid response is .no more dependent upon glucagon than the glucose response, since epinephrine blocks both.…”
Section: Discussionmentioning
confidence: 96%
“…We have found a rather marked late peak at ninety minutes with intrapancreatic glucagon infusion. 15 The two surges in secretory activity may reflect two types of release mechanisms or two separate storage compartments.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with the effect of glucagon in stimulating adenylate cyclase in liver, it was suggested that cyclic AMP was involved in the mediation of these effects. Since that time, many reports have confirmed the effects of glucagon on insulin release, and the similarities of action between those agents which raise intracellular cyclic AMP levels, such as glucagon, /3-adrenergic agents, phosphodiesterase inhibitors (papaverine, methylxanthines) and cholera toxin, and the effects of exogenous cyclic AMP or dibutyryl cyclic AMP have been noted [5][6][7][8][9][10][11][12][13][14]. It is clear from these reports that when the cyclic AMP concentration of the/3-cell is raised, by whatever means, the insulin response to glucose stimulation is enhanced.…”
mentioning
confidence: 94%
“…We observed a transient increase in plasma glucagon and insulin, with no apparent rise in plasma glucose. Glucagon increases insulin secretion in animal models 37,38 and humans, 39 via direct effects on glucagon receptors in β cells. 40 The transient insulin elevation with ING is therefore attributable to glucagon potentiation of insulin secretion rather than enhanced clearance.…”
Section: Discussionmentioning
confidence: 99%